2017
DOI: 10.3727/096368917x695416
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived mesenchymal stem cells from the elderly exhibit decreased migration and differentiation abilities with senescent properties

Abstract: Adipose-derived stem cells (ASCs) can be applied extensively in the clinic because they can be easily isolated and cause less donor-site morbidity; however, their application can be complicated by patient-specific factors, such as age and harvest site. In this study, we systematically evaluated the effects of age on the quantity and quality of human adipose-derived mesenchymal stem cells (hASCs) isolated from excised chest subcutaneous adipose tissue and investigated the underlying molecular mechanism. hASCs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 14 publications
3
19
1
6
Order By: Relevance
“…To further test whether age impacts the functions of ADSCs, we examined the osteogenic differentiation potential of ADSCs with Alizarin Red S staining assay. We found that, in agreement with previous reports (Liu et al, ), the differentiation potential was impaired in the old groups of ADSCs in comparison to the young cells (Figure a–b). However, we did not observe any significant correlation between the differentiation potential and BER efficiency or XRCC1 expression (Figure c–d).…”
Section: Introduction Results and Discussionsupporting
confidence: 93%
“…To further test whether age impacts the functions of ADSCs, we examined the osteogenic differentiation potential of ADSCs with Alizarin Red S staining assay. We found that, in agreement with previous reports (Liu et al, ), the differentiation potential was impaired in the old groups of ADSCs in comparison to the young cells (Figure a–b). However, we did not observe any significant correlation between the differentiation potential and BER efficiency or XRCC1 expression (Figure c–d).…”
Section: Introduction Results and Discussionsupporting
confidence: 93%
“…PGC1α lacks DNA‐binding activity but interacts with and coactivates several transcription factors including Nrf2, which controls constitutive and inducible expression of an array of antioxidant enzymes including SOD, GST, and catalase . Downregulation of PGC1α has been shown to affect the antioxidant response in Friedreich's ataxia and expression of PGC1α has been noted to be lower in adipose tissue‐derived MSC from elderly donors . Interestingly, MSC isolated from patients with PSP had fivefold lower levels of expression of PGC1α compared with control MSC and, in an induced pluripotent stem cell model of Parkinson's disease, S‐nitrosylation of the transcription factor myocyte enhancer factor 2c (MEF2C) contributes to mitochondrial dysfunction and apoptotic cell death via dysregulation of the PGC1α‐MEF2C transcriptional network , a mechanism which may have contributed to the decrease in PGC1α expression seen in MS‐MSC at baseline and in response to nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The adipose tissue was digested by 0.1% (weight/volume) collagenase type I (Sigma‐Aldrich, St Louis, MO) at 37°C for 60 minutes with gentle agitation, as described in previous studies . The suspension was filtered through a nylon mesh (100 mesh), followed by centrifugation at 1000 rpm for 10 minutes, and the final pellet was resuspended in culture medium.…”
Section: Methodsmentioning
confidence: 99%